Correlation Between Albuminuria and Spontaneous Platelet Microaggregate Formation in Type 2 Diabetic Patients - Araki, Shin-ichi; Matsuno, Hiroyuki; Haneda, Masakazu; Koya, Daisuke; Kanno, Yosuke; Itho, Junko; Kishi, Akio; Isshiki, Keiji; Sugimoto, Toshiro; Maegawa, Hiroshi; Kashiwagi, Atsunori; Uzu, Takashi (Diabetes care, 2009)
OBJECTIVE: Albuminuria in type 2 diabetic patients is a risk factor for cardiovascular disease. We investigated the correlation between albuminuria and spontaneous microaggregation of platelets (SMAP) formed under shear stress. RESEARCH DESIGN AND METHODS: The study subjects were 401 type 2 diabetic individuals (252 with normoalbuminuria and 149 with albuminuria) who were examined for SMAP under conditions of shear stress only (no agonist stimulation) and the reversibility of platelet microaggregation after stimulation with 1 μmol/l ADP, measured by a laser light-cattering method. Active glycoprotein IIb/IIIa (GPIIb/IIIa) and P-selectin expression levels on platelets as an index of platelet activation were measured by whole-blood flow cytometry. RESULTS: SMAP formation was noted in 53% of diabetic patients. All patients with SMAP showed an irreversible pattern of platelet microaggregates by a low dose of ADP. SMAP was observed in 75% of diabetic subjects with albuminuria and in 39% of those with normoalbuminuria. Multivariate logistic regression analysis identified urinary albumin excretion rate and brachial-ankle pulse-wave velocity as independent factors associated with SMAP. The degree of SMAP correlated with active GPIIb/IIIa (γ = 0.59, P < 0.001) and P-selectin (γ = 0.55, P < 0.001) expression levels. These early-activated platelet profiles were significantly inhibited in albuminuric patients with aspirin intake, although the effect was incomplete. CONCLUSIONS: Our study demonstrated an independent association between albuminuria and early changes in activated platelet profiles of type 2 diabetic patients. Further follow-up and intervention studies are needed to establish whether the inhibition of SMAP affects the course of cardiovascular disease in type 2 diabetic patients.